DEVELOPMENT OF DESIGN ACTIVITY IN CHILDREN IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Scientific journal of the Fergana State University, 2024)
This article provides information about the development of a sense of beauty, design activity, creativity and competencies in preschool children. It is shown that preschool age is an important period in the development of design activity.